Development and Application of a gp60-Based Subtyping Tool for Cryptosporidium bovis - Weijian Wang; Muchun Wan; Fang Yang; Na Li; Lihua Xiao; Yaoyu Feng; Yaqiong Guo (Microorganisms, 2021)
Cryptosporidium bovis is a common enteric pathogen in bovine animals. The research on transmission characteristics of the pathogen is hampered by the lack of subtyping tools. In this study, we retrieve the nucleotide sequence of the 60 kDa glycoprotein (GP60) from the whole genome sequences of C. bovis we obtained previously and analyze its sequence characteristics. Despite a typical structure of the GP60 protein, the GP60 of C. bovis had only 19.3–45.3% sequence identity to those of other Cryptosporidium species. On the basis of the gene sequence, a subtype typing tool was developed for C. bovis and used in the analysis of 486 C. bovis samples from dairy cattle, yaks, beef cattle, and water buffalos from China. Sixty-eight sequence types were identified from 260 subtyped samples, forming six subtype families, namely XXVIa to XXVIf. The mosaic sequence patterns among subtype families and the 121 potential recombination events identified among the sequences both suggest the occurrence of genetic recombination at the locus. No obvious host adaptation and geographic differences in the distribution of subtype families were observed. Most farms with more extensive sampling had more than one subtype family, and the dominant subtype families on a farm appeared to differ between pre- and post-weaned calves, indicating the likely occurrence of multiple episodes of C. bovis infections. There was an association between XXVId infection and occurrence of moderate diarrhea in dairy cattle. The subtyping tool developed and the data generated in the study might improve our knowledge of the genetic diversity and transmission of C. bovis.